Role of Particle Size on Flotation Kinetics of Turkish Sphalerite Ores - Bayat, Oktay; Ucurum, Metin; Poole, Colin (Asian Journal of Chemistry, 2016)
The effects of size distribution on the flotation behaviour of sphalerite have been investigated in terms of kinetic parameters. In experimental studies, sub-samples of a Turkish sphalerite ore were ground for different times using a laboratory ball mill. Timed batch tests were then undertaken using a pilot flotation column and the resulting recovery/time data were used in kinetic modelling. Results indicated that sphalerite floated rapidly at a medium particle size distribution (d80 = 0.125 mm in this case). In addition, a statistical analysis of data demonstrated that the flotation rate constant corresponded to a first-order model with rectangular distribution of floatabilities given by the equation